An Evolutionary Approach to Modelling Brain-Mind-Soul Dynamics - Davis, J.J. Joshua (Cosmos and History: The Journal of Natural and Social Philosophy, 2019)
In recent work a theory about the symbiosis between soul, mind & brain dynamics has been proposed that includes dark matter as a potential source carrier of spiritual values. This theory is conveyed with a systems view where the networks present in human brain dynamics can interface with a brain-like network in the planetary noosphere. This theory, unlike Teilhard de Chardin extends to different planetary realms and dissipates any religious biases in the conception of the noospheres, which are seen as evolutionary ontologies. We introduce the reader to the mathematical modelling to this symbiosis geared towards a better understanding of human cognition and consciousness and also as a framework for the development of truly intelligent and benevolent systems, systems with soul development like behaviour. Here, we also give a seminal taxonomy of brain states in different cortices which could be related to stressful or peaceful states of being via internal or external stimuli that can be hypothesised and measured via EEG as a means to advance this theory. Finally, we conclude with some of the potential repercussions associated with a catastrophic scenario for humanity versus a path correction that would lead to social harmony provided that we develop our human spiritual potential by developing the mastery in interacting with the noosphere via meditation or other practices. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->